HUBUNGAN PERAN PETUGAS DAN SIKAP DENGAN PERILAKU MASYARAKAT DALAM PENGELOLAAN SAMPAH RUMAH TANGGA - Angelia, Inge; Edison, Edison; Syahril, Suci; Handayani, Sri; Sary, Annisa Novita (Ensiklopedia of Journal, 2020)
Garbage is a serious problem that needs more attention. Household waste is the biggest contributor to the waste problem, especially municipal solid waste due to population density. The purpose of writing this article is to see the relationship between the role of officers, attitudes and behavior of household waste management in the city of Padang. This type of research is quantitative with cross sectional type, with 100 respondents. Research variables are the role of officers, attitudes and behavior of waste management. Research instruments using a questionnaire. Data were analyzed using Chi-Square Test. The results showed less than half of the people had bad behavior (46%) in household waste management. More than half of the people said that officers had no role (54%) and lacked attitude (5%) in waste management. there is a meaningful relationship between the role of the officer (p-value 0.005) on community behavior in household waste management. There is no significant relationship between attitudes (p-value 0.124) on community behavior in household waste management. there is a meaningful relationship between the role of officers on community behavior in household waste management. There is no meaningful relationship between attitudes towards community behavior in household waste management.